THE IMPACT OF ADVERTISEMENT ON CONSUMER BUYING BEHAVIOUR TOWARDS SMART PHONE IN KANYAKUMARI DISTRICT (International Journal of Food and Nutritional Sciences, 2022)
Advertisements stimulate the consumers to buy smart phones. Within few years the smart phones which was bought becomes outdated which leads to buy a new one, so the need for the smart is arisen continuously. Advertisements make demand for smart phone among the new consumers and also the existing consumers. Advertisements inform the customer about the new features of the smart phone which induce the consumers to buy it. This study aims at finding whether or not advertisements influence consumer’s buying behavior towards smart phone and also to know the impact of advertisement on consumer buying behavior towards smart phone. To analyse the impact of advertisement, Chi-square, t-test and ANNOVA have been used. 125 sample respondents were selected on the basis of multistage random sampling method.